Flat lens design using phase correction technique for horn antenna applications - Nur Hazimah Syazana Abdul Razak; Nur Shahira Mat Hussain; Nurul Hazlina Noordin; Syamimi Mardiah Shaharum; Ahmad Syahiman Mohd Shah; Mohamad Shaiful Abdul Karim (Universitas Ahmad Dahlan, 2021)
A design of a flat dielectric lens is presented in this study to enhance directivity of a pyramidal horn antenna. The horn antenna is proposed to cover frequency of medical imaging system, which is between 5 and 6 GHz, and dielectric lens is designed based on phase correction techniques. The spherical waves produced by conventional horn antenna is being transform to planar waves by resorting flat lens in order to achieve a highly directive radiation in the farfield region. This is done by drilling numerous holes with different diameters through the dielectric material to produce different phase delay. The radiation characteristics of the lens are simulated using CST Microwave Studio and then compared with measured results. The results showed a good performance for radiation pattern when the lens is attached. This proposed design shows a significant increment of sidelobe level and 3-dB beamwidth between 5 and 6 GHz.